Bottle Feeding in Children under Two Years of Age in Multan; A hospital based study (Medical Forum Monthly, 2024)
Objective: To explore the factors responsible for bottle-feeding practice among mothers of children less than two years of age in Multan region. Design: An observational cross-sectional study. Duration & Setting: The patients who were admitted in Pediatric ward and/or attending OPD at Children Hospital and The Institute of Child Health Multan from 1 January 2010 to 26 June, 2010 Materials and Methods: 450 mothers, feeding their children with bottle, were interviewed about their infant feeding practices. A predesigned questioner was used to get detailed information. Results: Bottle feeding was more prevalent in illiterate 98(48%) and poor education class mothers, lower social class women 109(45%), Multigravida 159(54%) and in the mothers between 26 to 30year of age 78(61%). More common causes of bottle feeding were complaint of insufficient milk by mothers 89(41%) and early baby illnesses 42(39.2%). Conclusion: In my study major determinants of bottle feeding are related to poverty and lack of education about breast feeding and proper weaning practices.